Magnetization enhanced the multiple magnetic domain-dominated resonance modes in stripe domain films. (1st January 2023) - Yu, Jing; Chen, Xiaowen; Wang, Fangzhou; Adam, Roman; Bürgler, Daniel E; Pan, Lining; Zhang, Jing; Cui, Yuanzhi; Li, Qiuyue; Liu, Meihong; Xu, Jie; Li, Shandong; et al.
Abstract: FeCoHf films with different Hf contents and thicknesses were deposited by composition-gradient sputtering. The results showed that the stripe domain (SD) structure emerges when the film thickness exceeds a critical thickness (220–330 nm), but the increase in introduced Hf leads to a decrease in magnetization, and in turn, the stripe phase weakens and eventually disappears. Dynamic measurements revealed magnetic domain-dependent resonant absorption spectra with up to seven resonance peaks, which have rarely been observed in magnetic film with an established SD structure. The number of resonant peaks can be controlled by the saturation magnetization of the film. Micromagnetic simulations indicate that multiple magnetic domain resonance modes can be attributed to the enhanced magnetization, which induces an increase in the magnetic domain wall volume. These results emphasize the pivotal role of magnetic domain dynamics in the framework of spintronic and microwave devices.